The Germans from Russia: documenting the immigrant experience in northern Colorado - Bastian, Dawn E. (Dawn Elaine), 1961-, author; Haworth Press, Inc., publisher (Colorado State University. Libraries, 2005)
The Sidney Heitman Germans from Russia Collection at the Colorado State University Libraries is named in honor of the late Dr. Heitman's years of research and teaching about Colorado's second largest ethnic group. Created to support his Germans from Russia in Colorado Study Project, active at the university in the late 1970s, the collection's centerpiece is the oral histories generated by the project. This article provides information on the collection and describes a digital project supported by an Institute of Museum and Library Services (IMLS) grant through the Colorado Digitization Project (CDP) to make a selection of the oral histories, transcripts, photos, project documentation, and the finding aid available online to researchers. In addition to providing access to more than 1,500 digital objects, project staff developed important metadata for their discovery, retrieval, and management using the Western States Dublin Core Metadata Best Practices and Encoded Archival Description (EAD).
Final, peer-reviewed manuscript.
Keywords: Colorado State University. Libraries; digital projects; Institute of Museum and Library Services; IMLS; Colorado Digitization Project; CDP; oral histories; Sidney Heitman Germans from Russia Collection